Vitamin D deficiency and neuropathic pain in chronic spinal cord injury: a cross-sectional study - Shi, Tengbin; He, Yanfeng; Yu, Zhengxi; Li, Jiandong (Frontiers in Nutrition, 2025)
BackgroundSpinal cord injury (SCI) often leads to neuropathic pain (NeP), severely impacting patients’ function and rehabilitation. Vitamin D deficiency, highly prevalent in SCI due to reduced sun exposure and mobility, has been implicated in NeP in other conditions, but its role in chronic SCI-related NeP remains unclear.MethodsThis cross-sectional study enrolled 182 adults with chronic traumatic SCI (≥6 month post-injury) currently admitted to 2 rehabilitation centers. Vitamin D status {serum 25-hydroxyvitamin D [25(OH)D]} was measured via high-performance liquid chromatography–tandem mass spectrometry (HPLC-MS/MS). NeP was diagnosed using the Douleur Neuropathique 4 (DN4) questionnaire (score ≥4/10) in combination with clinical assessment by a physician. Multivariate logistic regression, controlling for confounders (e.g., age, comorbidity, Charlson Comorbidity Index, CCI), injury severity (American Spinal Injury Association Impairment Scale, and AIS grade), assessed the association between vitamin D levels and NeP. Receiver operating characteristic (ROC) curve analysis was performed to identify a predictive cutoff.ResultsThe prevalence of NeP was 52.7% (96/182). Vitamin D deficiency or insufficiency [25(OH)D < 30 ng/mL] affected 64.8% (118/182) of participants. Lower vitamin D levels were strongly and independently associated with NeP risk. Individuals in the lowest vitamin D tertile (2.00–11.68 ng/mL) had significantly higher adjusted odds of NeP compared to those in the highest tertile (16.71–23.03 ng/mL) [adjusted odds ratio: 4.8, 95% CI: (3.4, 6.8), p < 0.001]. ROC analysis identified a serum 25(OH)D level <16.35 ng/mL as a predictive cutoff for NeP (area under the curve = 0.812, sensitivity 79.1%, specificity 71.9%).ConclusionVitamin D deficiency is highly prevalent and a strong, independent predictor of neuropathic pain in individuals with chronic SCI. These cross-sectional findings suggest routine screening for vitamin D deficiency might be indicated; however, interventional trials are needed to confirm a potential therapeutic role of vitamin D supplementation in managing SCI-related NeP.